2003
DOI: 10.1175/1520-0442(2003)016<3665:tiiodt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Indices of Daily Temperature and Precipitation Extremes in Europe, 1946–99

Abstract: Abstract:The principal aim of this paper is to analyze the trends of the multi-annual course of the selected characteristics of extreme precipitation, snow cover and atmospheric thunderstorms in the second half of the twentieth century in Poland. The results of these investigations show that in Poland it is only possible to determine a weak decreasing trend of extreme precipitation events in the S and especially in the SW part of the country. In northern Poland, opposite, although similarly weak, trends have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
581
3
31

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,003 publications
(708 citation statements)
references
References 25 publications
65
581
3
31
Order By: Relevance
“…This indicates that in regions where the total precipitation increases, the precipitation extremes are likely to increase, while in regions where the total precipitation decreases or remains constant, the precipitation extremes may not decrease or remain constant at annual and seasonal scales. That is in agreement with the results of Klein Tank & Können [6], who confirmed that at stations where the amount of annual precipitation increased, the extreme indices had similar changes, but for stations with a decreasing annual amount, there was no such amplified response of the precipitation extremes. The reason for inconsistency in the trends for total precipitation and precipitation extremes could also be associated with the number of rainy days and the rainfall intensity.…”
Section: Relationship Between Extreme and Total Precipitationsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that in regions where the total precipitation increases, the precipitation extremes are likely to increase, while in regions where the total precipitation decreases or remains constant, the precipitation extremes may not decrease or remain constant at annual and seasonal scales. That is in agreement with the results of Klein Tank & Können [6], who confirmed that at stations where the amount of annual precipitation increased, the extreme indices had similar changes, but for stations with a decreasing annual amount, there was no such amplified response of the precipitation extremes. The reason for inconsistency in the trends for total precipitation and precipitation extremes could also be associated with the number of rainy days and the rainfall intensity.…”
Section: Relationship Between Extreme and Total Precipitationsupporting
confidence: 92%
“…Vincent et al [5] found some increases in consecutive dry days but no change in consecutive wet days and a decrease in precipitation extremes (including R10, R20, RX1day and RX5day) for countries of the western Indian Ocean. Klein Tank & Können [6] analyzed trends in indices of climate extremes in Europe and confirmed that at stations where the annual amount increases, the extreme index has similar changes, but for stations with a decreasing annual amount, there is no such amplified response of the precipitation extremes. For China, Zhai et al [7] found that there is a small trend in total precipitation for China as a whole, but there are distinctive regional and seasonal patterns of trends, and there is a great similarity between the spatial patterns of trends in extreme and total precipitation.…”
Section: Introductionmentioning
confidence: 96%
“…ac.uk/cru/projects/emulate/public/EMULATE-INDICES-SOFTWARE.doc). Analysis of annual and seasonal exceedances of daily T max and T min 10th and 90th percentiles calculated with respect to the 1961 -1990 baseline period, which describe the number of moderately extreme cold days and nights and moderately extreme warm days and nights, respectively, have been studied for the entire period (1850-2005) and also for the other identified subperiods reported by other researchers [Frich et al, 2002;Yan et al, 2002;Klein Tank and Können, 2003;Mokssit, 2003;DellaMarta et al, submitted manuscript, 2006] at larger spatial scales.…”
Section: Assessment Of Long-term Changes In the Occurrence Of Temperamentioning
confidence: 99%
“…This effect might be potentiated by changing climatic conditions. The overall warming resulting in the proposed increase of warm extremes will enhance heat loads of the animals during summer months (Klein Tank and Kö nnen, 2003). In the present study, the relationship between incidences of veterinary treatments as an indicator for health and the THI as an indicator for heat stress was investigated.…”
Section: Discussionmentioning
confidence: 97%